The Effect of Pentosan Polysulphate (SP54) on the Fibrinolytic Enzyme System - A Human Volunteer and Experimental Animal Study - Marsh, N A; Peyser, P M; Creighton, L J; Mahmoud, M; Gaffney, P J (Thrombosis and Haemostasis, 1985)
Pentosan polysulphate causes an increase in plasminogen activator activity in plasma both after oral ingestion and after subcutaneous injection. The effect is greatest after 3 h and has disappeared by 6 h. Repeat doses by mouth over 5 days elicit a similar response. The recorded increase in activity is due largely to the release of tissue-type plasminogen activator (tPA) from the endothelium according to the antigen assay although there could be a small contribution from Factor XH-related “intrinsic” fibrinolysis induced in vitro. SP54 enhances activity ex vivo by a non-specific surface effect, and this phenomenon may contribute the increased levels of activity seen in vitro. Administration of SP54 to animals elicits a similar increase in activator activity, the intramuscular route being slightly more effective. Results with an inferior vena cava thrombosis model in the rat suggest that pentosan polysulphate may induce a thrombolytic effect.
Keywords: Pentosan polysulphate; Stimulation of fibrinolysis; Plasminogen activator; Rat thrombus model; Oral ingestion